CEO POLITICAL IDEOLOGIES AND PAY EGALITARIANISM WITHIN TOP MANAGEMENT TEAMS - CHIN, M. K.; SEMADENI, MATTHEW (Strategic management journal, 2017)
Research summary: We examine the influence of CEO and compensation committee liberalism on top management teams (TMT) pay arrangements. Given that politically liberal individuals tend to value egalitarianism, we test whether firms with liberal CEOs tend to (1) reduce pay dispersion among non-CEO executives; and (2) reduce pay gaps between CEO and non-CEO executives, and whether compensation committee liberalism moderates these relationships. We find some evidence of a direct effect of CEO liberalism on TMT pay arrangements as well as some interaction between CEO and compensation committee liberalism on the pay arrangements. This study provides a better understanding of the antecedents of TMT pay arrangements and empirical evidence showing the influence of values at the top of organization. Managerial summary: Do the values of the CEO and compensation committee influence the pay of other top managers? Our study provides evidence that political ideology affects top manager pay. We examine whether CEO liberalism produces more egalitarian pay arrangements among top managers, and whether the liberalism of the compensation committee affects that relationship. We find that CEO liberalism reduces differences in the total pay among top managers, but does not influence the difference between CEO total pay and the total pay of top managers. We also find that compensation committee liberalism strengthens the negative influence of CEO liberalism on differences in total pay among top managers. Finally, we find that CEO liberalism reduces the difference between CEO bonus pay and the bonus pay of other top managers.